2000
DOI: 10.1029/2000gl011389
|View full text |Cite
|
Sign up to set email alerts
|

Global maps of Rayleigh wave attenuation for periods between 40 and 150 seconds

Abstract: Abstract.Studies of seismic attenuation must account for the large amplitude deviations caused by elastic focusing of energy. In a new approach, we jointly invert phase and amplitude measurements of 19,000 minor arc Rayleigh waves between periods of 40 and 150 seconds. The simultaneous inversion ensures that attenuation and phase velocity are mutually consistent because the phase and focusing term of amplitude are modelled using a common elastic model. At the shortest periods the maps show a good correlation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 18 publications
3
56
0
Order By: Relevance
“…For example, the East European Platform is characterized by fast shear wavespeed and low attenuation while the Tyrrhenian Sea is characterized by slow shear wavespeed and high attenuation. These features suggest that the same factors, e.g., temperature, control both elastic wavespeeds and anelastic attenuation at shallow depths (Billien et al, 2000;Dalton et al, 2008). In addition, some areas, e.g., the Anatolian Plate, involve more complicated relations between shear wavespeed and attenuation.…”
Section: Comparisons With Previous Modelsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, the East European Platform is characterized by fast shear wavespeed and low attenuation while the Tyrrhenian Sea is characterized by slow shear wavespeed and high attenuation. These features suggest that the same factors, e.g., temperature, control both elastic wavespeeds and anelastic attenuation at shallow depths (Billien et al, 2000;Dalton et al, 2008). In addition, some areas, e.g., the Anatolian Plate, involve more complicated relations between shear wavespeed and attenuation.…”
Section: Comparisons With Previous Modelsmentioning
confidence: 98%
“…Frequencydependent phase and amplitude differences between observed and simulated seismograms (Laske and Masters, 1996;Ekström et al, 1997;Zhou et al, 2004) are simultaneously considered in the inversion in order to ensure a consistent treatment between anelastic attenuation and elastic focusing/defocusing (Billien et al, 2000). Synthetic seismograms are computed based on a spectralelement method (Komatitsch and Tromp, 1999;Peter et al, 2011), and Fréchet derivatives with respect to the model parameters are numerically calculated in a 3D background model based on adjoint methods (Lailly, 1983;Tarantola, 1984;Tromp et al, 2005;Liu and Tromp, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although several workers have demonstrated that robust body-wave (e.g., Bhattacharya et al, 1996;Komatitsch et al, 2002;Reid et al, 2001;Ritsema et al, 2002) and surface-wave (e.g., Billien et al, 2000;Dalton and Ekströ m, 2006;Romanowicz, 1991;Selby and Woodhouse, 2002) amplitude and polarization patterns can be derived from high-quality data to constrain velocity gradients, attenuation, and anisotropy structure, most tomographic studies of velocity structure are primarily based on wave travel time or phase delay inversions. Compared to amplitudes, travel time datasets possess little scatter, and they can be determined in a relatively straightforward manner.…”
Section: Data Types In Seismic Tomographymentioning
confidence: 99%
“…This strategy led to maps of both even-and odd-degree structure, that were used to construct the first global model of shear attenuation (Romanowicz, 1995). Billien et al (2000) and Selby & Woodhouse (2000; explicitly treated elastic focusing using a linear approximation derived from ray theory (Woodhouse & Wong, 1986). The contribution from focusing to the amplitudes of Rayleigh waves was found to be considerable, even for long periods between 70 s and 170 s. This motivated Billien et al (2000) to jointly invert phase and amplitude measurements of Rayleigh waves for degree-20 maps of phase velocities and attenuation.…”
Section: D Attenuation Modelsmentioning
confidence: 99%
“…Billien et al (2000) and Selby & Woodhouse (2000; explicitly treated elastic focusing using a linear approximation derived from ray theory (Woodhouse & Wong, 1986). The contribution from focusing to the amplitudes of Rayleigh waves was found to be considerable, even for long periods between 70 s and 170 s. This motivated Billien et al (2000) to jointly invert phase and amplitude measurements of Rayleigh waves for degree-20 maps of phase velocities and attenuation. However, being concerned that focusing may not be predicted with sufficient accuracy by current velocity models, Selby & Woodhouse (2002) decided not to account for elastic effects in their inversion for 3D shear attenuation.…”
Section: D Attenuation Modelsmentioning
confidence: 99%